Studi Empiris Pengaruh Nilai Sosial terhadap Perilaku Konsumen Pembelian Produk Lokal oleh Generasi Z - Dessy Dwiyanti (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Generation Z is the largest and most influential group of consumers in both national and global markets. This generation is closely connected to technology and information, is critical-minded, and places great emphasis on social and environmental aspects. These traits make social values an important factor in influencing consumer purchasing decisions among Gen Z. This study aims to examine the influence of environmental concern, social ethics and justice, and global social awareness on the consumer behavior of Indonesian Gen Z in purchasing local products. Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 4 software was employed as the data analysis technique and falls under the quantitative research method. A total of 81 Gunadarma University students participated as respondents by filling out a questionnaire. The findings indicate that Environmental Concern (X1) does not have a significant effect on the Consumer Behavior (Y) of Indonesian Gen Z in purchasing local products. However, Social Ethics and Justice (X2) and Global Social Awareness (X3) have a significant influence on the Consumer Behavior (Y) of Indonesian Gen Z in purchasing local products.